Different types of intuition at the workplace: an integrative review - Svenson, Frithiof; Pietrzak, Piotr; Launer, Markus A. (Business: Theory and Practice, 2023)
To make good decisions, employees must manage their own intuitions and be able to anticipate decision-making in their work environment. How well this is accomplished has significant consequences for the workplace. A closer examination indicates that individuals utilize various types of intuition. People’s work context is frequently omitted from studies on the use of intuition, resulting in a literature that omits vital aspects of decision-making. To assist applicable research in the workplace, our contribution to the management literature is a comprehensive overview of intuitive decision-making types. Current psychological assessment scales constitute a mature discipline, but they frequently lack the professional applications needed in business administration and economics. Considering this, the primary objective of this article is to assemble and assess many types of intuition and combine them into a new lens for research in the theory and practice of business using a multidimensional approach. It is comprised of rational choice theory, classical intuitive decision making, emotional decisions (gut feelings), fast heuristic decisions, unconscious thought, and anticipation. The overview of several scientifically proven measuring scales produces a theoretical foundation for future empirical study in business administration and economics based on these findings.